Two New Palaeologan Torneses - Cowell, Sam (KOINON: The International Journal of Classical Numismatic Studies, 2023)
Son and successor of Michael VIII Palaeologos, Andronikos II Palaeologos spent his first days in power undoing much of his father’s work. With a quiet funeral for Michael, so too lay to rest the dream of a reunified church. For Andronikos II was devoutly orthodox and whatever his other flaws may have been, he remained popular with the people due to his restoration of the Eastern Church. Besides reinstating previously removed ecclesiastical officials to their old offices, the emperor cultivated a scholarly atmosphere in Constantinople. Advisors and friends of the emperor such as Theodores Methochites and Nicephorus Chumnus helped to create the so-called Palaeologan Renaissance. Not every front was as successful as these, however. Andronikos’ hiring of the Catalan company mercenaries proved to be an utter disaster and saw destruction wherever the renegade company roamed. The emperor’s eastern front hardly proved better as Seljuk Turks overran the frontier. Even at home, the emperor faced tragic deaths in his family as the emperor’s son, heir, and co-ruler Michael IX died prematurely. Andronikos II later fought and lost a bitter seven-year-long year long civil war with his grandchild Andronikos III, himself the son of Michael IX. Finally, after a rather ineffectual yet lengthy rule at the helm of the Byzantine state for 46 years, the elderly Andronikos II forcibly retired to spend his final powerless days as emperor-monk.